Penggunaan Teknologi Gemini dalam Penyelesaian Tugas Makalah Mahasiswa Prodi PAI Angkatan 2022 UIN Raden Fatah Palembang - Ellsa Dinanda; Ibnu Rozali; Abdullah Idi (CV. Doki Course and Training, 2025)
Technological developments have changed the way students prepare academic assignments, including the use of Gemini technology. Students of the Islamic Religious Education Study Program, class of 2022, Raden Fatah State Islamic University, Palembang, have begun to utilize this technology to increase the effectiveness of searching for references, compiling arguments, and editing writing. This study aims to determine the benefits of using Gemini technology as well as the supporting and inhibiting factors in completing the paper assignments of students of the Islamic Religious Education Study Program, class of 2022. This study uses a qualitative method with a descriptive approach through observation, interviews, and documentation. Data analysis uses reduction, presentation, and verification techniques. The results of the study show that Gemini technology increases efficiency in searching for references, organization, and writing quality. Supporting factors include ease of understanding complex material and acceleration of reference searches. While inhibiting factors include lack of technical skills of students, unstable internet access